Pengembangan Aksesibilitas Transportasi Pariwisata Pulau Pramuka Kepulauan Seribu - Dilla Nur Fadilla; Fahrurozy Darmawan (Fakultas Pariwisata Universitas Pancasila, 2018)
The development of the tourism industry can not be separated from the development of transportation accessibility. Which although the location of the tour it is very good, the access and transportation is less adequate the tourist visit there will be very limited and just certain tourist groups who visit. The location that the researcher chose to research is the Pramuka islands. With the aim of the strategic planning of the accessibility development in support of Pramuka island tour. The designing of this research uses a mixed method. Basically, this method combines various techniques, philosophy and research design orientation. The collected data will be analyzed by using SWOT analysis followed by compiling an alternative strategy using matrix SWOT for development of tourism transportation accessibility of Pramuka island. Accessibility of tourism transportation of the Pramuka island’s view from and towards to the Pramuka island. By looking at the characteristic of the existing transportation system on the Pramuka island by servicing that can get by the tourists while using it. Based on the results of the SWOT analysis raises alternative strategies of making schedules and travel routes in the Pramuka island, making the safety procedure to every existing transportation. Conducting information to the transportation service providers in the importance of transportation licence and quality of human resources in the transportation scope.